Le développement de la presse électronique en Algérie : Des dispositifs aux pratiques journalistiques - Fatima Zohra Taiebi Moussaoui (L’Année du Maghreb)
This study presents and analyses the place of the on-line press in Algeria through an empirical approach. Our research discusses the different factors (legal, economic, politic…) affecting the emergence of these news web sites of information. In order to response to our interrogations and hypotheses about this new media and their professionals we have practice an empirical investigation using a qualitative approach (interview and observation) with editor in chiefs for online newspapers.